Directive Illocutionary Acts in The Pursuit of Happiness: A Pragmatic Analysis - I Dewa Ayu Eva Darmayanti; I Made Rajeg; Sang Ayu Isnu Maharani (Universitas Al-Qolam Malang, 2026)
This study examined the grammatical sentence forms and directive illocutionary acts found in The Pursuit of Happiness. It aimed to identify the grammatical forms used to realize directive utterances and classify the types of directive illocutionary acts found in the film’s dialogues. A qualitative descriptive method was employed, using the film and its script as data sources. Data were collected through documentation and note-taking techniques and analysed based on relevant theories of grammatical sentence forms and directive illocutionary acts. The findings revealed 21 directive utterances, consisting of 13 imperative, 6 interrogative, and 2 declarative forms. The analysis also identified eight types of directive illocutionary acts: ask, order, command, request, beg, invite, permit, and advise. Order occurred most frequently, with five utterances, followed by ask with four, while the other six types each occurred twice. The findings also showed that directive illocutionary acts were mostly realized through imperative forms, followed by interrogative and declarative forms. This study contributes to pragmatic research by demonstrating the relationship between grammatical sentence forms and directive illocutionary functions in film dialogue and provides a reference for analysing speech acts in audiovisual discourse.